Investment decision-making – a behavioural approach. (4th October 2010) - Shanmugasundaram, V.; Balakrishnan, V.
Investments are made with an avowed objective of maximising wealth. Investors need to make rational decisions for maximising their returns based on the information available by taking judgements free from emotions. Investors' behaviour is characterised by over excitement and overreaction in both rising and falling stock markets. Most of the investments and financial theories (Steinbacher, 2008) are based on the idea that everyone takes careful account of all available information before making investment decision. This research is conducted to analyse the factors influencing the behaviour of investors in capital market. Empirical evidence suggests that demographic factors influence the investors' investment decisions. This research article also investigates how investor interprets and acts on various capital market information to make informed investment decisions.